Refugi a Sant Miguel
Refugio en San Miguel por Cristian Cirici y Lluís Gascón, proyectado en 1984-1985 y emplazado en Ibizza.
Keywords: CIRICI, CRISTIAN; GASCON, LLUIS; ESPAÑA; IBIZA; REFUGIOS; VIVIENDAS EN LA COSTA; VIVIENDAS MEDITERRANEAS; VIVIENDAS